National stereotypes as a co-determinant of bilateral relations - Lovec, Marko (Teorija in praksa, 2016)
This is a preliminary study of the role played by national stereotypes in the relations between Western Balkan countries. According to a model that is proposed, stereotypes co-determine bilateral relations together with structural factors such as competition for political and economic resources, with physical distance serving as a proxy for the role of stereotypes as such and ethnic distance for the role of structural factors. The model is tested through a cross-country comparison of the indicators of stereotypes, physical and ethnic distance and developments in bilateral relations in the period 2014-2015. The results show an indicative correlation between relative stereotypisation, physical and ethnic distance and specific developments in bilateral relations, thus supporting the model.
Keywords: Bilateral relations; Bilateralni odnosi; Družbena razdalja; Foreign policy; Former Yugoslav republics; nacionalni stereotipi; Nekdanje jugoslovanske republike; Social distance; Stereotipi; Stereotypes; Zahodni Balkan; Zunanja politika